Konstruktioita ja verkkoja: Kaksi käyttöpohjaista kielioppimallia - Heinonen, Tarja Riitta; Vilkuna, Maria; Dubois, Gaïdig; Niva, Heidi (Virittäjä, 2022)
Arvioidut teokset Adele E. Goldberg: Explain me this. Creativity, competition, and the partial productivity of constructions. Princeton: Princeton University Press 2019. 195 s. isbn 978-0-691-17426-6. Holger Diessel: The grammar network. How linguistic structure is shaped by language use. Cambridge: Cambridge University Press 2019. 280 s. isbn 978-1-108-49881-4.